Polymeric nanoparticles and organic fluorophores for cancer sensing and therapy - Ang, Chung Yen (2016)
Cancer has been ranked as one of the top killer diseases around the world. Traditional therapeutic strategies often result in high side effect accompanied by the relatively low rate of survivability. More recently, various nano materials have been employed as delivery vehicle for the therapeutic agent, aiming to improve the therapeutic efficiency and at the same time, reducing the side effect experienced by the patient. Therefore, this research dissertation aims to provide a review on the various types of nanomaterials used in the biomedical field for cancer therapy application. With this, we have presented the synthesis and application of a polymer based nanoparticles for drug delivery application. We have extended this work to the in-vivo system and the nano formulation showed a positive effect on the tumor bearing nude mice. Apart from tackling the disease by developing an efficient system for therapeutic purposes, diagnostic strategies developments are also a key aspect that the biomedical societies are focusing on. In various research, it was found that the intracellular compartment of cancer cells express high level of glutathione (GSH). Therefore, the detection in the rise of GSH level in the cellular compartment could serve as an early indication of cancer. One of the common ways in the qualitative detection of GSH is by means of using a reaction base fluorescence probe. Fluorescence probe allow us to detect the target analyte in a highly selective manner without the use of sophisticated instruments. In the second part of this dissertation, we have presented the development of two different fluorescence probes for the detection of GSH and other biological thiol. In the first work, we have loaded the probe in a nano formulation that has shown positive response towards GSH in in vitro environment. In the second work, we have designed a fluorescence probe that could detect biological thiol and hydrogen peroxide in an orthogonal fashion without compromising its selectivity. This could even be achieved with the use of a single excitation source and the generation of a different output depending on the analyte presence in the solution of interest. With this added advantage, the probe could also be used to detect H2O2, which research has also shown that the H2O2 level also have certain correlation to other diseases. With these three chapters, this dissertation is then concluded. Future work could then be geared towards the development of a single nanoparticles system that encompassed both therapy and diagnostic functionality. In this way, it was realized that the polymeric based nanoparticles are highly customizable whereby a total different functionality could be expressed by a simple change in the building component. Therefore, much work could be done to explore the various possible applications with this class of novel materials.